The Role of Corporate Culture in Performance Measurement and Management System - Kotková Stříteská, Michaela; Zapletal, David (My University, 2020)
Recently, there has been increasing pressure to change current performance measurement and management systems from control systems to those that support learning and continuous improvement. This change requires a specific corporate culture that supports the e ective operation of performance measurement and management. This paper aims to clarify the relationship between corporate culture and performance measurement and management systems. Questionnaire survey data from Czech medium and large companies were collected and analyzed by Pearson’s chi-squared test to validate the proposed hypothesis. The research findings confirmed that performancemeasurement and management systems of companies that devoted sucient energy and attention to performance-driven culture are more e ectively developed. Analysis of di erent performance-driven culture attributes revealed which are the most important ones.
Role podnikové kultury v systémech měření a řízení výkonnosti
Keywords: performance measurement system; performance management; performance-driven culture; systém měření výkonnosti; řízení výkonnosti; výkonnostně řízená kultura